Defining renal phenotype in Alström syndrome. Issue 6 (10th October 2018) - Baig, Shanat; Paisey, Richard; Dawson, Charlotte; Barrett, Timothy; Maffei, Pietro; Hodson, James; Rambhatla, Srinivasa Bhargav; Chauhan, Priyesh; Bolton, Shaun; Dassie, Francesca; Francomano, Clair; Marshall, Robert P; et al.
Abstract: Background: Alström syndrome (AS) is a rare autosomal recessive ciliopathy with a wide spectrum of clinical features, including cone–rod retinal dystrophy, neuronal deafness, severe insulin resistance and major organ failure. The characteristics of renal disease in the syndrome have not been systematically described. The aim of this study is to define the onset and progression of renal disease in AS. Method: Prospective observational cohort study. Setting and Participants: Thirty-two adult subjects from a national specialist clinic in UK and 86 subjects from an international AS registry were studied. Outcomes: First, an international registry cross-sectional study across all age groups to determine change in kidney function was performed. Secondly, a detailed assessment was carried out of adult AS patients with serial follow-up to determine incidence, aetiology and progression of renal disease. Analytical approach: Generalized estimating equations were used to evaluate the relationship between age and estimated glomerular filtration rate (eGFR). Associations between patient factors and eGFR levels were then assessed in the adult AS cohort. Results: The international registry study of the renal function of 118 subjects with AS (median age 21 years) showed a rapid decline with age, at an average of −16.7 and −10.9 mL/min/1.73 m 2 per decade in males and females, respectively. In a UK national cohort of 32 patients with AS (median age 22 years), 20/32 (63%) had chronic kidney disease (CKD) Stage 3 or above based on eGFR <60 mL/min/1.73 m 2 or evidence of albuminuria. Hyperuricaemia was noted in 25/32 (79%). Structural abnormalities such as nephrocalcinosis without hypercalcaemia and cysts were observed in 20/32 (63%) subjects. Lower urinary tract symptoms were frequent in 17/19 (70%) of AS patients. Histological evidence showed mixed tubulo-interstitial and glomerular disease. Conclusions: This is the first study to demonstrate that renal disease is the hallmark of AS, which starts early and progresses with age, leading to a high prevalence of advanced CKD at young age. AS should be considered in the differential diagnosis of rare genetic renal diseases.